How Much Carbon Pricing is in Countries' Own Interests? : The Critical Role of Co-Benefits - Parry, Ian (IMF Working Papers; Working Paper, 2014)
This paper calculates, for the top twenty emitting countries, how much pricing of carbon dioxide (CO2) emissions is in their own national interests due to domestic co-benefits (leaving aside the global climate benefits). On average, nationally efficient prices are substantial, USD 57.5 per ton of CO2 (for year 2010), reflecting primarily health co-benefits from reduced air pollution at coal plants and, in some cases, reductions in automobile externalities (net of fuel taxes/subsidies). Pricing co-benefits reduces CO2 emissions from the top twenty emitters by 13.5 percent (a 10.8 percent reduction in global emissions). However, co-benefits vary dramatically across countries (e.g., with population exposure to pollution) and differentiated pricing of CO2 emissions therefore yields higher net benefits (by 23 percent) than uniform pricing. Importantly, the efficiency case for pricing carbon's co-benefits hinges critically on (i) weak prospects for internalizing other externalities through other pricing instruments and (ii) productive use of carbon pricing revenues.